Effect of dental caries and socioeconomic status on social capital throughout adolescence: a 6-year follow-up - Gabriela Figueiredo MEIRA; Jessica Klöckner KNORST; Marília Cunha MARONEZE; Fernanda Ruffo ORTIZ; Thiago Machado ARDENGHI (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The aim of the study was to investigate the influence of clinical and socioeconomic factors on social capital throughout adolescence. A cohort study was performed in 2012 (T1) with a random sample of 1,134 12-year-old adolescents from Santa Maria, Brazil. Questions on socioeconomic factors (maternal education, household income, household crowding) were answered by the parents. Clinicians evaluated their dental caries (decayed, missing, and filled status of permanent teeth) and gingival bleeding (using the Community Periodontal Index). Contextual variables including the mean income of the neighborhood in which the school was located were used (T1). The adolescents were revaluated in 2018 (T2) and answered questions regarding social capital (social trust, social control, empowerment, neighborhood security, and political effectiveness). A path analysis was used to test the relationship between the predictor variables (T1) and social capital (T2). A total of 768 adolescents were reevaluated at a 6-year follow-up (cohort retention rate of 67.7%). Most of the adolescents were girls, with a low household income, about 40% had caries experience (T1), and about 64% had high social capital (T2). The highest neighborhood's mean income was related to a lower household income in T1 (p < 0.01), and this was directly related to a low social capital in T2 (p = 0.04). Furthermore, caries experience at T1 was directly associated with low social capital at T2 (p = 0.03). Socioeconomic factors were also related to caries experience. Individuals who lived in neighborhoods with greater inequality such as families with a low household income and those with untreated dental caries in early adolescence, had a low social capital after follow-up.